Risk Factors Associated With Hypertension Among Individuals Aged 35–65 Years In The Working Area Of Namorambe Public Health Center, Deli Serdang - Eva Ellya Sibagariang; Mutiara Br Silalahi; Srivani Simanullang; Mafe Robbi Simanjuntak (Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension is a non-communicable disease that remains a major public health problem due to its increasing prevalence. Data on patient visits in the working area of Namorambe Public Health Center, Deli Serdang Regency, showed an increase in hypertension cases from 7,643 visits in 2024 to 8,100 visits in 2025. This study aimed to analyze the risk factors associated with hypertension among individuals aged 35–65 years in the working area of Namorambe Public Health Center. This study employed a quantitative design with a cross-sectional approach. The sample consisted of 93 respondents selected using simple random sampling. Data were collected through questionnaires and blood pressure measurements and analyzed using the Chi-Square test and multiple logistic regression. The results showed that most respondents experienced hypertension (67.7%). The majority of respondents had obesity nutritional status (45.2%), family history of hypertension (61.3%), unhealthy lifestyles (62.4%), moderate stress levels (50.5%), low physical activity (51.6%), and poor sleep quality (73.1%). Bivariate analysis indicated that nutritional status, lifestyle, physical activity, and sleep quality were significantly associated with hypertension, while family history and stress level were not significantly related. Multivariate analysis revealed that sleep quality was the most dominant factor associated with hypertension (OR=4.365).